Kyrgyz Republic : 2011 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kyrgyz Republic. (IMF Staff Country Reports; Country Report, 2011)
The Kyrgyz Republic is recovering from a deep political crisis. Agriculture, tourism, mining, and textile production will be important drivers of growth. Strong export-oriented growth and fiscal consolidation will help to reduce the current account deficit in the medium term. Executive Directors endorsed the authorities' structural reform agenda, emphasizing that steadfast implementation is critical to the success of the economic program; developments in the banking sector have exposed shortcomings in the bank resolution framework and the central bank's de facto lack of supervisory independence.